2013
DOI: 10.1073/pnas.1302935110
|View full text |Cite
|
Sign up to set email alerts
|

Preemptive priming readily overcomes structure-based mechanisms of virus escape

Abstract: A reverse-genetics approach has been used to probe the mechanism underlying immune escape for influenza A virus-specific CD8 + T cells responding to the immunodominant D b NP 366 epitope. Engineered viruses with a substitution at a critical residue (position 6, P6M) all evaded recognition by WT D b NP 366 -specific CD8 + T cells, but only the NPM6I and NPM6T mutants altered the topography of a key residue (His155) in the MHC class I binding site. Following infection with the engineered NPM6I and NPM6T influenz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…A diverse TCRαβ repertoire provides a greater range of TCR clonotypes with scope for the preferential selection of high-avidity TCRs into the immune response (25,26). This is a particular advantage for viral control, as diverse TCR repertoires with high pMHC avidity TCR clonotypes are potentially capable of recognizing newly emerging viral escape variants (27,28). Thus, preservation of TCRαβ clonal diversity within influenza-specific Trm cells in human lungs has important implications for effective control of viral infections, including influenza viruses.…”
Section: Discussionmentioning
confidence: 99%
“…A diverse TCRαβ repertoire provides a greater range of TCR clonotypes with scope for the preferential selection of high-avidity TCRs into the immune response (25,26). This is a particular advantage for viral control, as diverse TCR repertoires with high pMHC avidity TCR clonotypes are potentially capable of recognizing newly emerging viral escape variants (27,28). Thus, preservation of TCRαβ clonal diversity within influenza-specific Trm cells in human lungs has important implications for effective control of viral infections, including influenza viruses.…”
Section: Discussionmentioning
confidence: 99%
“…The B*27-NP 383 anchor mutation is reminiscent of, or in some senses comparable to, the prevalent mouse D b -NP-N5H escape variant from our experimental study, whereby an anchor mutation has become fixed in seasonal isolates leading to the loss of an immunogenic peptide from the available pool of T cell antigens. Importantly, prior priming with the PR8-NP-N5H virus, and the subsequent recall with the HK-NP-N5H virus, was unable to overcome this virus escape mechanism, unlike the stimulation for escape at TCR contact residues 40 . As a consequence, the generation of anchor escape variants should be avoided by vaccination procedures that use viral peptides or live viruses.…”
Section: Discussionmentioning
confidence: 99%
“…Since the 3D7 and 7G8 dimorphic variations occur between these anchor residues on position 4 (A*03) and position 3 (B*58), it is possible that these variations in 7G8 abrogate recognition by TCRs induced against the 3D7 epitope, supporting this first hypothesis. Moreover, studies of escape mutations in influenza virus have shown that some mutations eliminate binding to MHC, while other mutations retain the ability to bind to MHC but are no longer recognized by the TCR recognizing the wild type peptide [ 21 , 22 ]. In chronic HIV infections, escape mutations that abrogate MHC binding completely are found more frequently, as such escape mutations provide the pathogen with permanent protection from T cell recognition, while pathogens with TCR escape mutations are still vulnerable to new T cell populations arising that recognize the mutation [ 23 ].…”
Section: Discussionmentioning
confidence: 99%